Response Strategies of Root System Architecture to Soil Environment: A Case Study of Single-Species Cupressus funebris Plantations - He, Wenchun; Luo, Chao; Wang, Yang; Wen, Xiaochen; Wang, Yu; Li, Tianyi; Chen, Gang; Zhao, Kuangji; Li, Xianwei; Fan, Chuan (Frontiers in Plant Science, 2022)
Root system architecture (RSA), being a key characteristic of the root economic spectrum, describes the spatial arrangement and positioning of roots that determines the plant's exploration of water and nutrients in soil. Yet, it remains poorly understood how the RSA of woody plants responds to the demand of water and nutrients in different soil environments and how the uptake of these resources is optimized. Here we selected single-species plantations of Cupressus funebris and determined their topological index (TI), revised-topological index (qa and qb), root link length (RLL), root branching rate (Rb and Ri:Ri+1), and in situ soil physico-chemical properties, to assess which foraging strategies roots adopt in different soil environments among Guang’an City (GA), Suining City (SN), Mianyang City (MY), and Deyang City (DY) in China. Principal component analysis (PCA) showed that levels of soil nutrients was the highest at DY, followed by MY and SN, and lower at GA. A dichotomous branching pattern was observed for GA, SN, and MY, but a herringbone branching pattern for DY. The RLL was ranked as GA>SN>MY>DY. The Rb of GA, SN and MY was significantly lower than that of DY (p<0.05). Among the different city regions, values of R1/R2 were the largest in different regions and those of R4/R5 the smallest. The cross-sectional area of the root system did not differ between any two connected branch orders. The TI, qa and RLL were significantly and negatively correlated with soil’s water content, porosity, total nitrogen, total potassium, available nitrogen, and available phosphorus (p＜0.05), whereas they all had significant, positive relationships with soil temperature (p＜0.05). The Rb was significantly and positively correlated with total potassium in soil (p＜0.05). Redundancy analysis showed that total potassium was the main factor driving variation in RSA. Our results emphasize that the root system architecture is capable of corresponding plastic alterations by changing its number of internal or external links and the root link length of fine roots vis-à-vis a heterogeneous environment, thereby optimizing rates of water capture and space utilization, to ensure the normal metabolism and growth of plants.